2009
DOI: 10.1093/alcalc/agp044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tryptophan Metabolism on the Vulnerability to Alcohol-Related Blackouts and Violent Impulsive Behaviours

Abstract: Put together, these findings support the validity of the BOVIB criterion to differentiate a sub-group of vulnerable AD subjects and suggest that OTL may help to concurrently define a specific endophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Therefore, KYN metabolites may contribute to the aggression/impulsivity and neurocognitive deficits proposed as endophenotypes associated with suicidal behavior (Mann, 2009). A possible relationship between KYN and impulsivity is also suggested by two studies finding that KYN was strongly elevated (7-fold) in patients with a history of violent impulsive behaviors and alcohol-related blackouts (Vignau, 2010). Relationships between KYN, its metabolites, and behavioral phenotypes were not assessed in this study but should be tested in future studies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, KYN metabolites may contribute to the aggression/impulsivity and neurocognitive deficits proposed as endophenotypes associated with suicidal behavior (Mann, 2009). A possible relationship between KYN and impulsivity is also suggested by two studies finding that KYN was strongly elevated (7-fold) in patients with a history of violent impulsive behaviors and alcohol-related blackouts (Vignau, 2010). Relationships between KYN, its metabolites, and behavioral phenotypes were not assessed in this study but should be tested in future studies.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, suicide risk is elevated among patients being treated with cytokines for medical problems, as seen in individual case histories (Baron, 1993; Janssen, 1994); in a case series of patients with multiple sclerosis who developed suicidal ideation (n=11) or made suicide attempts (n=4), and whose suicidality remitted after withdrawal of the interferon (Fragoso, 2010); and in a prospective study of patients with hepatitis C who experienced increased suicidal ideation over 8 weeks (Dieperink, 2004). KYN may be involved in other types of violent behavior apart from suicide attempts, according to two different research groups who have observed increased KYN plasma levels in antisocial violent offenders (Tiihonen, 2001) and in alcoholics with a history of blacked-out violent impulsive behaviors (Vignau, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Some amino acids are correlated with violence in previous studies, especially tryptophan [67], which is the amino acid precursor of 5-HT biosynthesis [13]. A study of violent criminals found the plasma content of the amino acid tryptophan and other large neutral amino acids were increased [67][68][69]; however, much more studies have reported decreased tryptophan is correlated with aggressive behaviours [15,[70][71][72]. Instead of finding the plasma tryptophan as a differential metabolite, we found phenylalanine, tyrosine and tryptophan biosynthesis was a differential metabolic pathway between the schizophrenia patients with and without violence, which support amino acids play an important role in regulating violence.. We found vanillylmandelic acid, involved in tyrosine metabolism, was increased in V.SC, which is consistent with an earlier study reporting tyrosine supplements increased aggressive behaviours in mice [17].…”
Section: Discussionmentioning
confidence: 95%
“…Sublette et al (2011) is the first report of an association between KYN levels and history of suicide attempts among individuals with MDD. KYN may be involved in other types of violent behavior apart from suicide attempts, according to two different research groups who observed increased KYN plasma levels in antisocial violent offenders (Tiihonen et al, 2001) and in alcoholics with a history of blacked-out violent impulsive behaviors (Vignau et al, 2010). This study tested two a priori planned contrasts and found that mean plasma KYN levels were higher in MDD suicide attempters compared with MDD nonattempters.…”
Section: Case Controlmentioning
confidence: 89%